Human Resource Empowerment And Training Patterns In Supporting The Creative Economy In MSMES Bintang Mas Sumenep - Endang Widyastuti; Syaiful Anwar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
MSMEs actors have the potential to contribute to improving the regional and national economy. However, many MSME actors still do not receive maximum training. The aim of this research is to analyze how the training patterns and human resource empowerment patterns carried out by Bintang Mas MSMEs in Sumenep Regency support the development of the creative economy. The method used in this research is a qualitative approach. Data collection techniques use observation, interviews and documentation. The data analysis techniques used in this research are data collection, data reduction, data presentation and drawing conclusions. The result of this research is empowerment carried out by Bintang Mas, namely by recruiting workers who are dominated by the community around the Bintang Mas MSME. In this case, it is the community in Kasengan Village. One of the main reasons is to help improve the family economy and increase income for local residents. Then, the pattern of human resource training for MSME Bintang Mas players is on the job training, namely the owners of MSME Bintang Mas directly provide training to their workforce at the workplace while carrying out work in each section.